Sexual function and satisfaction of women with vaginismus - (:unkn) unknown (Kare Publishing, 2012)
Sexual function and satisfaction of women with vaginismus Objective: Vaginismus is one of the sexual dysfunctions that affects couples' sexual life. There is a common opinion that women with vaginismus have a satisfied sexual life even there is no vaginal entry. But contrary to this opinion, several studies reported that sexual function and satisfaction of women with vaginismus were impaired. In our study, our purpose was to evaluate sexual function and satisfaction in women with vaginismus and to compare the findings with that of healty women's. Method: Forty women with vaginismus who referred to Sexual Dysfunction Therapy Outpatient Unit and fifty healthy voluntary women who had no sexual complaint participated in the study. Questionnaire regarding demographic characteristics, Symptom Check List (SCL-90 R), Cloninger's Temperament and Character Inventory (TCI), Golombok-Rust Inventory of Sexual Satisfaction (GRISS) were evaluated. Results: It was found that women with vaginismus avoided sexual intercourse, were more emotional and needed approval more frequently. Also, vaginismus history was more frequent in their family and among close relatives. They found inadequate their and their partners' level of sexual knowledge. They had typical fears and they had problems in all other domains of sexual function as well as the vaginal entry. There were statistically significant differences in GRISS vaginismus, avoidance, satisfaction, frequency, lack of orgasm subscales and total GRISS score between vaginismus and control groups. Conclusions: Unlike general opinion, women with vaginismus have problems in many domains of sexual function. We think that it would be inadequate if vaginismus is considered only a problem of vaginal entry, that all domains of sexual function, avoidance and enviromental factors should be evaluated together.
Keywords: Anorgasmia; Character features; Frequency of sexual intercourse; Sexual satisfaction; Vaginismus